Role of the Phytochemical Compounds like Modulators in Gut Microbiota and Oxidative Stress - Martínez, Yordan; Más, Dairon; Betancur, Cesar; Gebeyew, Kefyalew; Adebowale, Tolulope; Hussain, Tarique; Lan, Wensheng; Ding, Xinghua (Current Pharmaceutical Design, 2020)
Background: Currently, daily consumption of green herb functional food or medicinal herbs has increased as adopted by many people worldwide as a way of life or even as an alternative to the use of synthetic medicines. Phytochemicals, which are a series of compounds of relatively complex structures and restricted distribution in plants, usually perform the defensive functions for plants against insects, bacteria, fungi or other pathogenic factors. A series of studies have found their effectiveness in the treatment or prevention of systemic diseases such as autoimmune diseases, cancer, neurodegenerative diseases, Crohn's disease and so on. Objective: This review systematizes the literature on the mechanisms of the phytochemicals that react against unique free radicals and prevent the oxidative stress and also summarizes their role in gut microbiota inhibiting bacterial translocation and damage to the intestinal barrier and improving the intestinal membrane condition. Conclusion: The gut microbiota modulation and antioxidant activities of the phytochemicals shall be emphasized on the research of the active principles of the phytochemicals.
Keywords: gut microbiota